Sustainable by Ideology? The Influence of CEO Political Ideology and Ivy League Education on ESG (Environmental, Social, and Governance) Performance - Tim Heubeck; Annina Ahrens (Business Strategy and the Environment, 2025)
Building on upper echelons theory, this study posits that political ideology serves as a foundational factor influencing whether CEOs prioritize environmental, social, and governance (ESG) outcomes, whereas Ivy League education acts as a contextual factor that moderates this relationship. Analyzing data from S&P 900 manufacturing firms, the findings reveal that liberal CEOs enhance ESG performance—particularly in the social and governance pillars—in contrast to their conservative counterparts. CEO political ideology's effect on ESG performance does not depend on whether CEOs graduated from an Ivy League institution. Instead, Ivy League–educated CEOs directly deter ESG performance, possibly due to specific values, perspectives, and social connections shaped by their elite educational background. This study contributes to upper echelons theory by illuminating two critical microlevel factors—CEO political ideology and elite education—that shape firms' ESG strategy, offering valuable implications for boards and stakeholders when selecting and evaluating corporate leadership.
Keywords: 650; CEO; elite education; ESG; Ivy League; political ideology; upper echelons theory